The relationship between growth, development and social milieu - a longitudinal study involving preschool Coloured children in Cape Town - Molteno, Christopher D (Department of Paediatrics and Child Health, 2018)
A prospective longitudinal study was carried out to establish the relationship between growth, development and social milieu in Coloured pre-school children in Cape Town. This population was selected because, on the basis of previous studies, a wide range of nutritional status as well as a spectrum of socio-economic conditions were known to exist. A pilot study was conducted to establish the feasibility of obtaining information about factors to be included in the study as well as to determine the most suitable sampling methods. A cohort of 1 000 consecutive Coloured infants born in the Cape Town municipal area and notified to the Cape Town City Council was identified. A random sample of 187 was selected from the cohort for long-term study. Anthropometric data were documented from birth until 5 years and compared to the NCHS reference values. Developmental data consisted of milestones recorded during infancy, language assessment on the Reynell Language Scale at 2½ years carried out by the Logopaedics Department, University of Cape Town, and at 5 years, a specially constructed developmental assessment designed to assess gross motor function, fine motor development including visuo-motor skills and language, both comprehension and expression as well as basic colour and number concepts. Social data were collected during home visits by two experienced, full-time research social workers, who were both integrally involved in the planning of the study. At birth infants were relatively light and short for gestational age. Size at birth correlated with social class. A rapid post-natal weight gain rendered them relatively overweight between 3 and 6 months. Thereafter they again became lighter and shorter than the NCHS reference values and this persisted during the pre-school period. Mother's weight was related to weight at birth, 12 months and 30 months. The genetic influence on growth was reflected in a correlation between parental height and child's length from 12 months onwards. Environmental influences as assessed by social class by occupational grading of the breadwinner, income and family stability were also correlated with growth from 12 months onwards. Infant development as indicated by milestones was very similar to internationally reported studies. Motor development was not associated with social class by occupational grading of the breadwinner but with father's education, mother's personality and family stability. It was also highly correlated with growth during infancy. Early language milestones were associated with the child's micro-environment as indicated by marital status, family unit, setting and stability. Language development at 30 months reflected a general lag in verbal skills and was correlated with parental education and family stability. At five years there was a good correlation between growth, development and social milieu, although the social variables accounted for far more of the variation in development than did growth. Social class by occupation grading of the breadwinner and income reflected the general socio-economic status and there was a good cross-correlation between the social variables. Approximately one third of the families lived in a middle cl ass environment. However, poor maternal education, low incomes and over-crowding were prevalent and must constitute risk factors in child rearing. Sixty five percent of the mothers were not educated further than primary school level and over half of the families were living below an effective minimum level of income. Similarly, over half the families lived in grossly overcrowded conditions. In conclusion, therefore, during infancy developmental milestones were similar to those reported in the literature. Later, however, there was a fall-off in development and this coincided with a greater association with social circumstances. Just prior to school entry social factors far outweighed growth indices as predictors of developmental variation. Social stability of the family a composite evaluation based on a number of social characteristics, was most consistently associated with development. The implications for intervention are that this would need to be broad based and aimed at improving incomes, housing, family cohesion and child centredness and eliminating social pathology. Such intervention would require a concerted effort from a variety of sources which should include administrators, community workers and health professionals.